(untitled) (Journal of Maternal and Child Health, 2023)
Background: Untreated pregnancy anxiety can have a significant impact on the pregnancy and postpartum outcomes. Causing mental disorders during pregnancy has an increased risk and adverse effects on the mother and fetus. Mindfulness Based Cognitive Therapy (MBCT) can increase awareness about the function of thought patterns in daily activities and is able to control awareness of thoughts, feelings and body gestures that can affect anxiety levels and cortisol hormones in the body. This study aimed to examine the effect MBCT to reduce anxiety in 3rd trimester of pregnant women. Subjects and Method: This was a randomized controlled trial. A sample of 20 pregnant women divided into two groups. Intervention group was MBCT with 8 sessions for 30 minutes each session within a period of 2 weeks. The control group was health education and usual care. The dependent variable was anxiety. The independent variable was MBCT. Anxiet was measured using HARS questionnaires. Difference of anxiety between groups were tested using independent t-test. Results: Mean of anxiety score in the MBCT group (Mean= 16.40; SD= 4.01) was lower than in the control group (Mean= 23.60; SD= 7.37), and it was statistically significant (p = 0.015). Conclusion: MBCT is effective to reduce anxiety in 3rd trimester of pregnant women. Keywords: Mindfulness Based Cognitive Therapy, pregnancy, anxiety. Correspondence: Sundari. Master’s Program of Applied Midwifery, Health Polytechnics, Ministry of Health Semarang. Jl. Tirto Agung, Pedalangan, Banyumanik, Semarang, Central Java 50268. Email: sundarisst3@gmail.com. Mobile: 0821-7591-9584.